Find me - Aciman, André (Farrar, Straus and Giroux, 2019)
In this spellbinding exploration of the varieties of love, the author of the bestseller "Call Me by Your Name" revisits its complex and beguiling characters decades after their first meeting. No novel in recent memory has spoken more movingly to contemporary readers about the nature of love.